2007
DOI: 10.1002/psc.845
|View full text |Cite
|
Sign up to set email alerts
|

Induction of macrophage migration through lactose‐insensitive receptor by elastin‐derived nonapeptides and their analog

Abstract: Elastin, one of the extracellular matrix components, is present in tissues requiring extensibility and resilience such as the aorta, lungs, ligaments and skin. Degradation of elastin is observed in diseases such as atherosclerosis, emphysema and metastasis. It has been suggested that degraded elastin-derived peptides interact with a variety of cell types and are involved in development of diseases. Two nonapeptides, Ala-Gly-Val-Pro-Gly-Leu-Gly-Val-Gly (AGVPGFGVG) and Ala-Gly-Val-Pro-Gly-Phe-Gly-Val-Gly (AGVPGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…14 Intimal macrophages, involved in the pathogenesis of atherosclerosis, form foam cells and are CD11c positive but 5-LO negative. 14 Macrophages are attracted to the aortic wall by elastin degradation products 15 ; CC chemokines (monocyte chemoattractant protein-1 ͓MCP-1͔ and RANTES͓regulated on activation, normal T cell expressed and secreted͔) 16 -18 ; and granulocyte macrophage colony stimulating factor. 19 MCP-1 and RANTES are CC chemokines which have been found to increase during experimental development of AAA, using the elastase model.…”
Section: Macrophagesmentioning
confidence: 99%
“…14 Intimal macrophages, involved in the pathogenesis of atherosclerosis, form foam cells and are CD11c positive but 5-LO negative. 14 Macrophages are attracted to the aortic wall by elastin degradation products 15 ; CC chemokines (monocyte chemoattractant protein-1 ͓MCP-1͔ and RANTES͓regulated on activation, normal T cell expressed and secreted͔) 16 -18 ; and granulocyte macrophage colony stimulating factor. 19 MCP-1 and RANTES are CC chemokines which have been found to increase during experimental development of AAA, using the elastase model.…”
Section: Macrophagesmentioning
confidence: 99%
“…Primary rat macrophage isolation was performed as previously described (31). Wistar rats (12-to 20-wk-old males) were injected with 20 ml of 2% glycogen (Sigma-Aldrich).…”
Section: Isolation Of Rat Macrophagesmentioning
confidence: 99%
“…9,20 We used a 10 Ϫ8 M concentration of VGVAPG, which was previously shown to be most effective in the induction of macrophage migration and aggregation and dendritic cell fusion. 8,9 The addition of the elastin-derived hexapeptide induced almost a 2-fold increase in the rate of macrophage fusion ( Figure 4A-C), resulting in the generation of some giant cells containing more than 200 nuclei ( Figure 4D). …”
Section: Elastin-derived Hexapeptide (Vgvapg) Increases Macrophage Fumentioning
confidence: 99%
“…Previously, it has been shown that this peptide has a diverse biological activity, including an induction of macrophage migration and aggregation and dendritic cell fusion. 8,9 To show the relevance of MGCs in our mouse model compared with human diseases, we performed immunostaining of human tissues for cathepsin K and observed cathepsin K-positive MGCs in the carotid arteries and abdominal aortic aneurysms. …”
mentioning
confidence: 99%